PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN - Muhamad Syaeful Anwar (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to examine the effect of product quality, price perception, and brand image on customer satisfaction when using Xiaomi/Oppo/Vivo/Samsung brand smartphones. This study used a quantitative approach because testing the hypothesis. The sampling technique uses purposive sampling with the criteria of people who use Xiaomi/Oppo/Vivo/Samsung brand smartphones. The data collection technique uses a self-administered survey by distributing questionnaires directly to respondents using Google Forms. Respondents in this study are 204 respondents. The data analysis technique uses SmartPLS version 3.3. The results show that product quality, price perception, and brand image has a positive and significant effect on customer satisfaction. Keywords: Product Quality, Price Perception, Brand Image, Customer Satisfaction